2002
DOI: 10.1128/iai.70.9.5335-5337.2002
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia High-Pathogenicity Island Contributes to Virulence in Escherichia coli Causing Extraintestinal Infections

Abstract: The Yersinia high-pathogenicity island (HPI) encodes an iron uptake system mediated by the siderophore yersiniabactin (Ybt) and confers the virulence of highly pathogenic Yersinia species. This HPI is also widely distributed in human pathogenic members of the family of Enterobacteriaceae, above all in extraintestinal pathogenic Escherichia coli (ExPEC). In the present study we demonstrate a highly significant correlation of a functional HPI and extraintestinal virulence in E. coli. Moreover, using a mouse infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
120
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(135 citation statements)
references
References 18 publications
(22 reference statements)
6
120
4
Order By: Relevance
“…The HPI was first described in Yersinia spp., but has also been described in other Enterobacteriaceae (Bach et al, 2000;Koczura & Kaznowski, 2003;Mokracka et al, 2004;Petermann et al, 2008;Schubert et al, 1998Schubert et al, , 2000Schubert et al, , 2002. Yersinia spp., Escherichia coli, and possibly K. pneumoniae isolates containing the HPI are more virulent than isolates lacking this island (Bearden et al, 1997;Carniel et al, 1992;de Almeida et al, 1993;Lin et al, 2008;Schubert et al, 2002). The HPI was recently shown to be transferable by conjugation with HPI-ICEKp1 (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The HPI was first described in Yersinia spp., but has also been described in other Enterobacteriaceae (Bach et al, 2000;Koczura & Kaznowski, 2003;Mokracka et al, 2004;Petermann et al, 2008;Schubert et al, 1998Schubert et al, , 2000Schubert et al, , 2002. Yersinia spp., Escherichia coli, and possibly K. pneumoniae isolates containing the HPI are more virulent than isolates lacking this island (Bearden et al, 1997;Carniel et al, 1992;de Almeida et al, 1993;Lin et al, 2008;Schubert et al, 2002). The HPI was recently shown to be transferable by conjugation with HPI-ICEKp1 (Lin et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Indisputable evidence that HPI increased the virulence of the EHOS is lacking. However, in all Enterobacteriaceae tested, virulence was significantly increased by the HPI (Bearden et al, 1997;Carniel et al, 1992;de Almeida et al, 1993;Lin et al, 2008;Schubert et al, 2002). Other genes associated with the EHOS were those previously described on the pLVPK virulence plasmid of K. pneumoniae CG43 (Chen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial number of both groups contained genes involved in the formation of different adhesins, including P (various pap genes and alleles) and type 1 fimbriae. APEC and UPEC isolates also contained many genes related to iron acquisition, including fyuA and irp-2, genes of the yersiniabactin operon (Oelschlaeger et al, 2002a;Pelludat et al, 1998;Schubert et al, 1998Schubert et al, , 2000Schubert et al, , 2002; iucC and iutA, genes of the aerobactin operon ; iroN of the salmochelin operon (Russo et al, 2002;Hantke et al, 2003); and sitA of the sit operon (Runyen-Janecky et al, 2003). They also had a high prevalence of genes related to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from plasmid-borne factors, genes encoding for ferric yersiniabactin uptake (fyuA) and iron-repressible protein (irp2) have been detected by PCR in more than 65% of strains isolated from cases of avian colibacillosis (Janssen et al, 2001). Subsequent work has shown that production of yersiniabactin contributes to virulence of exPEC and Klebsiella pneumoniae in mice (Schubert et al, 2002;Lawlor et al, 2007). Additionally, chuA (encoding a haeme utilization/transport protein) was detected by screening a signature-tagged mutagenesis bank of APEC O2 in chickens (Li et al, 2005), suggesting a role in virulence.…”
Section: Progress Towards Unravelling Apec Virulence Factorsmentioning
confidence: 99%